Valorisation of phenolic compounds from grape pomace - Lima, Vasco José Costa de (2017)
Every year millions of tonnes of waste are generated by the food industry. Producing wine is major cultural and economical activity but is also responsible for a large amount of waste in a short period of time. Grape pomace is the main by-product, a cheap material known for being rich in phenolic and other valuable compounds. This work aimed at optimizing the conditions (duration, temperature, solid:liquid ratio and concentration of the enzyme) for sequential extractions (water and acetone-based) process from red and white grape pomace (Vitis vinifera cultivars Merlot and Garganega, respectively) with the addition of five enzymes (Pectinex Ultra-SPL, Pentopan Mono BG, Celluclast, Driselase and Viscozyme). Several classes of extracted compounds (total phenolic content, protein, reducing sugars, tannins, flavonoids, anthocyanins and flavanols) were then quantified by spectrophotometric assays and specific phenols identified and quantified through a chromatographic technique. The optimum determined conditions for the extraction apllied to the assays were 2 hours, 50 ºC, 1:10 solid:liquid ratio and 2% enzyme concentration. Results obtained reveal that doing sequential extractions allowed for the recovery of more content for the extracts. It also showed some differences between both grape pomaces. Also, using enzymes was beneficial for achieving higher extracted phenolic content. The findings show that grape pomace is a good source for phenolic compounds that can be exploited as ingredients for application on the food, pharmaceutical or cosmetic industries.